Correction: Publisher Correction: Base excision repair AP endonucleases and mismatch repair act together to induce checkpoint-mediated autophagy - Tanima SenGupta (Nature Portfolio, 2018)
Nature Communications 4: Article number: 2674 (2013); Published online 24 October 2013; Updated 29 March 2018 The original HTML version of this Article had an incorrect article number of 2578; it should have been 2674. This has now been corrected in the HTML; the PDF version of the Article was correct from the time of publication.